Vesicle-based cell-free synthesis of short and long unspecific peroxygenases - Walter, Ruben Magnus; Zemella, Anne; Schramm, Marina; Kiebist, Jan; Kubick, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Unspecific peroxygenases (UPOs, EC 1.11.2.1) are fungal enzymes that catalyze the oxyfunctionalization of non-activated hydrocarbons, making them valuable biocatalysts. Despite the increasing interest in UPOs that has led to the identification of thousands of putative UPO genes, only a few of these have been successfully expressed and characterized. There is currently no universal expression system in place to explore their full potential. Cell-free protein synthesis has proven to be a sophisticated technique for the synthesis of difficult-to-express proteins. In this work, we aimed to establish an insect-based cell-free protein synthesis (CFPS) platform to produce UPOs. CFPS relies on translationally active cell lysates rather than living cells. The system parameters can thus be directly manipulated without having to account for cell viability, thereby making it highly adaptable. The insect-based lysate contains translocationally active, ER-derived vesicles, called microsomes. These microsomes have been shown to allow efficient translocation of proteins into their lumen, promoting post-translational modifications such as disulfide bridge formation and N-glycosylations. In this study the ability of a redox optimized, vesicle-based, eukaryotic CFPS system to synthesize functional UPOs was explored. The influence of different reaction parameters as well as the influence of translocation on enzyme activity was evaluated for a short UPO from Marasmius rotula and a long UPO from Agrocybe aegerita. The capability of the CFPS system described here was demonstrated by the successful synthesis of a novel UPO from Podospora anserina, thus qualifying CFPS as a promising tool for the identification and evaluation of novel UPOs and variants thereof.